Analisis perilaku “baku bawa” pada pasangan ibu hamil dengan HIV/AIDS di Papua - Pratami, Yustika Rahmawati; Vitania, Wiwit; Hasnia, Hasnia; Astutik, Eftyaningrum Dwi Wahyu; Handayani, Endah Purwanti; Palino, Keryn Amanda (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: The shift in HIV test results in pregnant women from negative to positive during pregnancy indicates a gap in the implementation of the PMTCT program, primarily because HIV testing is generally only performed once on pregnant women and does not optimally involve partners. The practice of